Antibacterial and Antioxidant Effect from Nanoparticle of Andrographis paniculata Extract on Wistar Rat Infected with Listeria monocytogenes - Nawasyifa Atmaja; Neni Susilaningsih; Helmia Farida (Medica Hospitalia : Journal of Clinical Medicine, 2025)
BACKGROUND: Listeria infection triggers the production of ROS (Reactive Oxygen Species) and radical-waste accumulation such as Malondialdehyde (MDA). Andrographis paniculata, triggers the production of Superoxide Dismutase (SOD) as antioxidant and suppresses the bacteria multiplication in host’s body. However, these active-phytochemical have poor destruction due to their large size and molecular weight. Nanoparticle technology may overcome this problem to increase bioavailability and benefit of herbal pharmacology. AIMS:  to evaluate the effectivity nanoparticle of A. paniculata extract to increase bacteria elimination, increase SOD level, and reduce MDA level in rat infected with L. monocytogenes METHOD: Experimental research with post-test only controlled trial design was conducted using white rats (Rattus novergicus strain Wistar) into Normal (N), Negative Control (K-), A. paniculata extract (EAP-200), and Nanoparticle of A. paniculata extract Group (nEAP-100, nEAP-200, and nEAP-400). Colony was measured using total plate count method. SOD & MDA level were measured using colorimetric method RESULT:  L. monocytogenes bacterial count from group with extract A. paniculata was significantly lower than those in negative control (p<0,05). SOD level from group with extract A. paniculata was very significantly higher than those in negative control (p<0,01), while MDA level from group with extract A. paniculata was very significantly lower than those in negative control (p<0,01). Dose of 200 mg/kgBW in nanoparticle form was the most optimum dose. CONCLUSION: Extract of A. paniculata at various doses and form, increase bacterial clearance, increase SOD level, and reduce MDA level in rat infected with L. monocytogenes.